AB1344 'CLINICAL ASSESSMENT OF THE MUSCULOSKELETAL SYSTEM' HANDBOOK AND ACCOMPANYING VIDEOS: 15 YEARS OF USE. (June 2019) - Li, Cheuk Yin; Wakefield, Sophia; Andrew, Donna; Coady, David; ,
Abstract : Background: 15 years ago, Arthritis Research UK (ARUK) produced the 'Clinical Assessment of the Musculoskeletal (MSK) System' handbook and a set of accompanying videos; 'Regional Examination of the Musculoskeletal System'.(1) There has been an evaluation of the use of this resource showing that they are widely used among medical students and healthcare professionals. Recently, ARUK has merged with Arthritis Care to create Versus Arthritis, and previous publications are due to be rebranded. Objectives: This project aims to review how the handbook and videos are being used 15 years on. The secondary aim is to gain insight into any changes that may need to be made going forward as Versus Arthritis seeks to revise and update the original materials. Methods: In September 2018, a clinical group was formed to review the current handbook's content and format. The project team was invited to take part in the surveys and disseminate them within their professional networks and across every UK medical school. Results: 78 people took part in the survey; this included 61 users (students and trainees) and 17 medical school teachers. User Survey: ' How to access the handbook? ' respondents said online (36%), via an app (31%) or printed version (10%). 83% of respondents said they found the handbook very useful, 100% said it was easy to understand, 95% said it was well illustrated, and 75% said the video clips were very useful. 100% of respondents said the handbook did not contradict any previous teaching received. When asked what would improve the handbook, the most popular response was case studies. When asked what the most useful thing was, most respondents commented on the structure and how clear and concise it was. When asked what the least useful thing was, respondents felt it lacked detail regarding the rationale behind the purpose of the examinations. Teacher Survey: 17 medical school representatives completed the survey. 94% of respondents use the resource. Most provide their students with the online version of the handbook (64%). 88% thought the resource was very useful for their students. 94% said the resource maps well to the current MSK curriculum. When asked what would improve the handbook the most popular response was abnormal examination findings. The least popular response was patient exercise videos and sheets. Content Review: Several comments were made suggesting the use of more appropriate language. Recommendations were made to introduce sections on physical activity, self-management and the multidisciplinary team involvement. A suggestion was made to include the patient's 'ideas, concerns and expectations' concept. Conclusion: The consensus is that the resource is already very good and maps well to the MSK curriculum taught by the medical schools. It would benefit from adding new contents, e.g. examination clips of patients with pathology. We would need to be wary of overcomplicating the purpose of the new resource. It was also highlighted that the resource would benefit from a refresh of the layout, including clear headings and more up to date images and diagrams. Several comments were made around the format to include an online resource that students could use to incorporate examination videos with experts explaining the findings. References: [1] Arthritis Research UK. 2018. Information for Health Professionals and Students. [Online] Available at: https://www.arthritisresearchuk.org/shop/products/publications/information-for-medical-professionals.aspx [Accessed 30 January 2019]. Acknowledgement: Louise Warburton, Ana Onebieni, Singh Harjinder, Pippa Watson, Mark Lilicrap, Anita Williams, Sarah-Jane Ryan, Jade Pullen, Stephanie Saltford Disclosure of Interests: Cheuk Yin Li: None declared, Sophia Wakefield: None declared, Donna Andrew: None declared, David Coady Grant/research support from: Currently, hold a grant of £10, 000 from Biogen, Consultant for: Yes as part of Medical Board for Internis, Speakers bureau: Yes, multiple speaker fees for a variety of companies